PENGEMBANGAN CANVA BERBANTUAN PBL UNTUK MENINGKATKAN MINAT BELAJAR SISWA DI UPT SD NEGERI 060793 MEDAN MAIMUN. - Riska Julinda; Ahmad Landong; Indah Humairoh; Dela Sisi Arina Sihombing; Fauziah Apriyani Rangkuti; Adinda Lestari; Atina Rahmi Nasution (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Education requires innovative learning media to enhance students' interest, motivation, and active participation in the learning process. The rapid development of educational technology encourages teachers to integrate digital media into classroom instruction to create meaningful and engaging learning experiences. However, the learning process at UPT SD Negeri 060793 Medan Maimun was still dominated by conventional teacher-centered methods, resulting in low student participation, limited interaction during lessons, and reduced learning interest, particularly in the Pancasila Education subject. These conditions indicate the need for innovative instructional media that can support student-centered learning while improving learning outcomes and motivation. Therefore, this study aimed to develop Canva-based learning media integrated with the Problem Based Learning (PBL) model and to determine its validity, practicality, and effectiveness in improving elementary school students' learning interest.This study employed the Research and Development (R&D) method using the ADDIE development model, which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. The research participants were 18 fifth-grade students at UPT SD Negeri 060793 Medan Maimun. Data were collected through classroom observations, interviews with teachers, questionnaires, documentation, and expert validation sheets involving media and material experts. The collected data were analyzed using descriptive quantitative techniques to evaluate the validity, practicality, and effectiveness of the developed learning media. The findings revealed that the Canva-based learning media integrated with the Problem Based Learning model fulfilled the established criteria of validity, practicality, and effectiveness. Expert validation results indicated that the media was highly suitable for classroom implementation, while teacher and student responses demonstrated that the media was practical and easy to use. Furthermore, the implementation of the developed media significantly increased students' learning interest, classroom participation, enthusiasm, motivation, and engagement throughout the learning activities. Students became more active in discussing problems, expressing opinions, collaborating with peers, and completing learning tasks. In conclusion, the Canva-based learning media integrated with the Problem Based Learning model is an innovative and effective instructional alternative that supports interactive, student-centered learning and contributes to improving students' learning interest in Pancasila Education at the elementary school level.